2018
DOI: 10.3389/fneur.2018.00539
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Cortical Structure and Functional MRI Connectivity in High Functioning Autism

Abstract: Autism spectrum disorders (ASD) represent a complex group of neurodevelopmental conditions characterized by deficits in communication and social behaviors. We examined the functional connectivity (FC) of the default mode network (DMN) and its relation to multimodal morphometry to investigate superregional, system-level alterations in a group of 22 adolescents and young adults with high-functioning autism compared to age-, and intelligence quotient-matched 29 healthy controls. The main findings were that ASD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 152 publications
(219 reference statements)
8
63
0
Order By: Relevance
“…Our regional analysis harnessed MRI-based cortical thickness measures, a reliable technique that has previously been applied to profile morphological variations across a broad spectrum of typical and atypical neurodevelopment (Raznahan et al, 2011). Surface-wide comparisons between ASD and TDC revealed increased cortical thickness in the former, with strongest effects in temporal and posterior midline regions, together with tendencies for prefrontal thickening, which is consistent with prior surface-and voxel-based data suggestive of diffuse grey matter increases in individuals with ASD (Bedford et al, 2019;Hong et al, 2017;Khundrakpam et al, 2017;Pereira et al, 2018;Raznahan et al, 2010;Scheel et al, 2011;Valk et al, 2015;Wallace et al, 2010). Although the ASD and TDC differences resembled those seen when comparing individuals with ANX to TDC, confirmed by spin tests that control for the shared spatial autocorrelations in two surface-based maps (Alexander-Bloch et al, 2018), ANX presented with a different distribution of anomalies with increased cortical thickness in frontoinsular-opercular regions while temporal and midline parietal were only visible at uncorrected significance level.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our regional analysis harnessed MRI-based cortical thickness measures, a reliable technique that has previously been applied to profile morphological variations across a broad spectrum of typical and atypical neurodevelopment (Raznahan et al, 2011). Surface-wide comparisons between ASD and TDC revealed increased cortical thickness in the former, with strongest effects in temporal and posterior midline regions, together with tendencies for prefrontal thickening, which is consistent with prior surface-and voxel-based data suggestive of diffuse grey matter increases in individuals with ASD (Bedford et al, 2019;Hong et al, 2017;Khundrakpam et al, 2017;Pereira et al, 2018;Raznahan et al, 2010;Scheel et al, 2011;Valk et al, 2015;Wallace et al, 2010). Although the ASD and TDC differences resembled those seen when comparing individuals with ANX to TDC, confirmed by spin tests that control for the shared spatial autocorrelations in two surface-based maps (Alexander-Bloch et al, 2018), ANX presented with a different distribution of anomalies with increased cortical thickness in frontoinsular-opercular regions while temporal and midline parietal were only visible at uncorrected significance level.…”
Section: Discussionsupporting
confidence: 86%
“…Cortical thickness provides biologically meaningful insight regarding the cellular and synaptic organization of the cortex (Desrivieres et al, 2014;Huttenlocher, 1979;Schuz and Palm, 1989). Previous studies have reported varied patterns and directions of cortical anomalies in ASD relative to typically developing controls (TDC) (Khundrakpam et al, 2017;Redcay, 2007;Pereira et al, 2018;Raznahan et al, 2010;Scheel et al, 2011;Wallace et al, 2010); however, recent large-scale studies based on open datasets have generally converged on increased thickness in frontal and temporal cortical areas in individuals with ASD (Bedford et al, 2019;Hong et al, 2017;Valk et al, 2015). Studies assessing cortical morphology in ANX have also pointed to increased cortical thickness in medial and lateral frontal regions relative to TDC (Gold et al, 2017;Strawn et al, 2014), with, however, a seemingly different spatial topography compared to ASD.…”
Section: Introductionmentioning
confidence: 99%
“…A major difficulty in the neurobiological understanding of autism is that the condition impacts multiple scales of brain organization [4][5][6][7][8][9][10] . Contemporary neuroimaging studies suggested that autism is characterized by both macroscale anomalies in brain connectivity [6][7][8][10][11][12][13][14] and local changes in microcircuit function such as excitation/inhibition imbalance 4,5,9,[15][16][17] . However, we currently lack an overarching framework that can bridge the topographical changes at macroscale and microscale dysfunctions in autism pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Systems neuroscience has recently gained unprecedented opportunities to interrogate the human brain at multiple scales in both health and disease 4,6,8,9,18 . Although a wealth of studies in autism spectrum conditions have examined local disturbances in cortical morphology 12,19 and functional connectivity 6,10,14,20,21 as well as mesoscale functional miswiring [22][23][24][25] , less is known about macroscopic changes in structural connectivity [26][27][28][29] . Previous studies observed atypical diffusivity parameters and streamline connections in local brain regions and pathways in autism 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes of the brain have been identified in patients with ASD in the literature: Sparks et al found children with ASD have significantly in-creased cerebral volumes compared with typically developing (TD) and delayed developing (DD) children [2]. Pereira et al found changes in cingulate gyrus, paracentral lobule and superior frontal gyrus on subjects with ASD [3].…”
Section: Introductionmentioning
confidence: 99%